PENGARUH TIPE INDUSTRI, PROFITABILITAS, MEDIA EXPOSURE, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP CARBON EMISSION DISCLOSURE (Studi Empiris Pada Perusahaan Non Industri Jasa Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016) - Endang Pujiastuty Nainggolan; Bill J. C. Pangayow; Anthonius H.C Wijaya (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to obtain empirical evidence on the analysis of factors affecting the voluntary disclosure of carbon emissions in companies in Indonesia. Factors used include industry type, profitability, firm size and leverage. Measurement of carbon emission disclosure levels using content analysis. There are 18 items to detect disclosure rates of carbon emissions. The population of this research is all financial data of non service industry companies listed on BEI period 2014-2016.Sampling method used in this research is purposive sampling method. The sample used in this research is non service industry which publishes annual and financial report during observation period anddiscloses carbon emission. The total sample used in this research is 27 companies. The data used is secondary data from IDX. The analysis technique used is multiple linear regression analysis. The results of this study indicate that industry type and company size have an effect on carbon emission disclosure, while profitability proxy with return on asset and return on equity and leverage have no effect on carbon emission disclosure